UJI TUBEX UNTUK DIAGNOSIS DEMAM TIFOID DI LABORATORIUM KLINIK NIKKI MEDIKA DENPASAR - Ida Bagus Verry Kusumaningrat; I Wayan Putu Sutirta Yasa (Universitas Udayana, 2014)
Typhoid fever is one of the endemic diseases that commonly occur in rural and urban communities. It spreads through food and drink contaminated bySalmonella typhi bacteria. In 2008, detection of typhoid fever was carried out usingthe tubex test in which it principally detects the IgM antibody that specific forSalmonella typhi O9 present in serum by employing the method of InhibitionMagnetic Binding Immunoassay (IMBI). The present study was aimed to evaluateresults of blood sample examination of suspected typhoid fever patient using thetubex test, in order to confirm the typhoid fever diagnose. This research wasretrospective study by analyzing 1.266 data of suspected patients obtained from NikkiMedika Clinic Laboratory. The samples were delivered to the Clinic Laboratory forlaboratory examination since 2008 till October 2012. Each sample was examinedusing the tubex test. The results showed that 11.6 – 27.8% of the blood samples werepositive for typhoid fever while 70 – 88.7% was negative.